NILAI-NILAI KARAKTER DALAM PERMAINAN TRADISIONAL ANAK JUNGKIT JUNGKITAN - Ni Putu Eni Astuti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Children world is identical to games. Lately traditional game is left and replaced by the emerging of technology. This paper aimed at describing jungkit-jungkitan traditional game activity in character education review. Commonly this game is played by boys in coupled group, in sitting position on each of the player instep, while moving from start to finish. This study was a qualitative descriptive research involving elementary school children in Buahan Village, Tabanan, Bali. The data was collected through interview and observation. Data analysis used content analysis upon the procedure of jungkit-jungkitan game and data from interview and observation on the children. The validation was conducted by expert discussion. The finding showed that jungkit-jungkitan traditional game embraced the four-character education pillars, i.e. (1) intellectual development, (2) affective development, (3) spiritual and emotional development, and (4) physical and kinesthetic development. Majority the developed character values in jungkit-jungkitan traditional game was on the pillar of physical and kinesthetic development, i.e. discipline, sportive, tough, reliable, endurance, cheerful, persistent, hardworking, and competitive.